Determinants of overweight or obesity among ever-married adult women in Bangladesh. Issue 1 (December 2016) - Sarma, Haribondhu; Saquib, Nazmus; Hasan, Md; Saquib, Juliann; Rahman, Ahmed; Khan, Jahidur; Uddin, Md; Cullen, Mark; Ahmed, Tahmeed
Abstract Background The prevalence of overweight and obesity is increasing in Bangladesh. It is higher among Bangladeshi women than among men. This study was conducted to assess a host of demographic and socioeconomic correlates of overweight and obesity, separately for the urban and rural women of Bangladesh. Methods We used data from the Bangladesh Demographic and Health Survey (BDHS) 2011. The BDHS provides cross-sectional data on a wide range of indicators relating to population, health, and nutrition. We analyzed nutrition-related data to identify the factors associated with being overweight or obese among ever-married women aged 18–49 years. Results Of 16, 493 women, about 18 % (95 % CI 17 · 80–18 · 99) were overweight or obese. Unemployed urban women were at 1 · 44 (95 % CI 1 · 18–1 · 76, p < 0 · 001) times higher risk of being overweight or obese than those women who were involved in manual-labored work. Watching television at least once a week was another significant predictor among urban women (OR 1 · 49; 95 % CI 1 · 24–1 · 80;p < 0 · 001) and rural women (OR 1 · 31; 95 % CI 1 · 14–1 · 51;p < 0 · 001). Household wealth index and food security were also strongly associated with overweight or obesity of both rural and urban women. Conclusions The findings of the study indicate that a large number of women in Bangladesh are suffering from being overweight or obese, and multiple factors are responsible for this including, older age, being from wealthy households, higher education, being from food-secured households, watching TV at least once a week, and being an unemployed urban woman. Given the anticipated long-term effects, the factors that are associated with being overweight or obese should be considered while formulating an effective intervention for the women of Bangladesh.